Application of Mirror Therapy to Muscle Strength in Non-Hemorrhagic Stroke Patients: A Case Study - Sartiya Rini, Dewi; Sulupadang, Prishilla; Saranani, Muhaimin; Mudin, Abu Iqra (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Background: One of the therapies that can be used in non-hemorrhagic stroke patients to increase muscle strength is mirror therapy. Mirror therapy is a form of rehabilitation or distance exercise that relies on the patient's motor imagination and imagination using a mirror as a visual stimulation that can be imitated by the part of the body that is disturbed. The mirror stimulates cortical and spinal motors. The parts of the body that are affected tend to mimic mirror reflections, which aids in the recovery process of the extremities. This study aims to apply mirror therapy to physical mobility in non-hemorrhagic stroke patients. Methods: A descriptive case study on one subject, namely Mrs. S who was diagnosed with a non-hemorrhagic stroke with major nursing problems of physical mobility disorders and was given mirror therapy. The mirror used is 35x30x20 cm for the upper extremities and 30x55x30 cm for the lower extremities. This therapy is carried out for 8 days with a frequency of 1x a day which is done in the afternoon for 30 minutes every day. The ethical approval was issued by the Ethics Commission of the Kendari Ministry of Health's Polytechnics. Results: After being given mirror therapy to Mrs. S for 8 days, physical mobility increased with the value of the muscle strength of the lower left extremity from 2 to 4 while the upper left extremity did not experience an increase due to more severe nerve damage in the upper left extremity Conclusion: Physical mobility improved in Mrs. S with the administration of mirror therapy for 8 days. This therapy can be applied in health services, especially in stroke patients with limb weakness.